Aerogel based on protein fiber composite few-layer MXene as well as method and application thereof
By using protein fiber composite oligolayer MXene aerogel material in a solar interface evaporator, the problems of poor stability of photothermal materials, high cost of matrix materials and insufficient long-term operation capabilities are solved, and efficient and stable photothermal conversion and water evaporation effects are achieved.
Patent Information
- Application Number
- CN202411724026.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-28
AI Technical Summary
Existing solar interface evaporators have problems such as poor stability of photothermal materials, high cost of matrix materials and insufficient long-term operation capabilities.
Aerogel preparation method based on protein fiber composite oligolayer MXene was adopted to obtain aerogel materials with stable and directional pore structures through electrostatic adsorption strategies and directional frozen casting.
It improves the stability and photothermal conversion efficiency of the photothermal layer, enhances salt resistance and evaporation rate, and reduces operating and maintenance costs.
Smart Images

Figure CN119746736A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of interfacial evaporation water treatment and heavy metal adsorption, and in particular to an aerogel based on protein fiber composite oligolayer MXene, a method and an application thereof. Background Art
[0002] Desalination of seawater is a feasible way to obtain a large amount of fresh water. However, most of the current desalination methods use membrane distillation and reverse osmosis, which consume a lot of fossil energy and are not conducive to environmental sustainable development. Solar interfacial evaporation has low cost and high efficiency, and is a promising method for producing fresh water. A solar interfacial evaporator is a device that uses solar energy to drive water evaporation. Through efficient photothermal conversion, it converts light energy into thermal energy and concentrates the heat at the water-air interface, thereby maximizing the evaporation efficiency. It has potential application prospects in the fields of seawater desalination, wastewater treatment or salt extraction. Therefore, it has attracted the interest of many researchers. For example, Chinese patent CN202311487004.2 discloses a solar interfacial evaporator based on amyloid plant protein fiber aerogel, its preparation method and application, and soy protein isolate powder is subjected to fiberization treatment and SPI-AF-Gel aerogel is obtained by directional freezing and steam cross-linking strategy; then, a polypyrrole photothermal coating is grown in situ on the surface of SPI-AF-Gel aerogel by in situ polymerization to obtain SPI-AF-Gel@PPy solar interfacial evaporator. Although some progress has been made, existing solar interface evaporators may have the following problems:
[0003] (1) Poor stability of photothermal materials: As the core component of solar interfacial evaporators, photothermal materials directly affect the evaporation rate and photothermal conversion efficiency of evaporation devices. For example, MXene, as a two-dimensional semiconductor photothermal material, has shown broad application prospects in the field of interfacial evaporation due to its excellent light absorption and photothermal conversion capabilities. However, in actual use, MXene is easily oxidized in air or water environments, resulting in a decrease in its light absorption performance, thereby reducing the photothermal conversion efficiency.
[0004] (2) High cost of the base material of the interface evaporator: Currently, the base materials used to prepare the solar interface evaporator are mostly petroleum-based polymers. With the increasing shortage of global oil resources and the improvement of environmental protection requirements, oil prices have shown an upward trend, which has led to a continuous increase in the cost of raw materials for petroleum-based polymers. In addition, traditional petroleum-based polymers will degrade during use, producing microplastics or other pollutants, which in turn cause serious damage to the environment.
[0005] (3) Insufficient long-term operation capacity of the interfacial evaporator: Most aerogels are prepared by a simple freeze-drying method, which forms a disordered porous structure. However, this disordered pore arrangement is not conducive to the effective reflux of salt in interfacial evaporation applications. During long-term evaporation, salt tends to accumulate on the surface of the evaporator and gradually block the pore channels. This phenomenon not only hinders the transmission of water, but also reduces the light absorption efficiency, ultimately leading to a decrease in the evaporation performance of the evaporator, which has an adverse effect on its long-term stable operation.
[0006] Therefore, it is necessary to develop a protein fiber composite oligolayer MXene aerogel and its preparation method and application to solve the above problems. Summary of the invention
[0007] In view of this, the present invention provides a method for preparing a protein fiber composite oligolayer MXene aerogel to solve the problem of poor photothermal conversion efficiency or evaporation rate caused by poor stability of photothermal material coating in existing evaporators.
[0008] The present invention adopts a preparation method based on protein fiber composite oligolayer MXene aerogel, which is characterized by comprising the following steps:
[0009] S101: taking 2-8 wt.% pea protein suspension solution and fibrillating it to obtain starch protein fiber suspension;
[0010] S102 prepares 5 mg / mL-10 mg / mL MXene suspension;
[0011] S103 uses an electrostatic adsorption strategy to in-situ deposit starch protein fibers on the MXene surface to obtain a precursor mixture, and the pH of the precursor mixture is 1-3;
[0012] S104 performs directional freeze casting and gas phase crosslinking on the precursor mixture to obtain an aerogel material.
[0013] Preferably, PPI-AF@MXene-Gel aerogel is prepared by ice template freeze drying: the PPI-AF@MXene solution is poured into a customized copper ice template mold with a diameter of 3.5 cm, and directionally frozen in a liquid nitrogen environment at -196°C for 30-60 minutes, and then placed in a freeze dryer for 2-3 days to obtain PPI-AF@MXene aerogel, which is cross-linked in an oven at 40°C using 25% glutaraldehyde vapor for 4 hours to obtain pea protein isolate starch fiber-based PPI-AF@MXene-Gel aerogel.
[0014] Preferably, in step S101, the pea protein isolate is dissolved in ultrapure water containing NaCl, and then the pH of the solution is adjusted to 1-3 with hydrochloric acid, and then hydrated at 4°C for 16 hours, centrifuged at 10000 rpm for 20 minutes, and filtered to remove insoluble matter to obtain a pea protein isolate solution with a mass concentration of 2wt.%, and then stirred at 250 rpm in an oil bath at 85°C for 16 hours, cooled in an ice bath, and incubated at room temperature for 1 day to obtain a starch protein fiber solution.
[0015] Preferably, in step S102, LiF is weighed and completely dissolved in a hydrochloric acid solution to prepare an etching solution, and then Ti3AlC2 is slowly added to the etching solution, and the mixture is continuously stirred for 24 hours at 28°C and then washed until the pH of the mixture becomes 7. After the reaction is completed, the reaction product is washed several times to make the pH value of the reaction product neutral, and then transferred to a clean and dry flask, filled with argon, ultrasonicated in an ice bath for 2 hours, and then centrifuged for 1 hour, and the upper suspension is collected to obtain a MXene suspension solution with a concentration of 8 mg / mL.
[0016] Preferably, in step S103, 8 mL of starch fiber solution and 1 mL of MXene suspension solution are weighed and stirred to mix evenly to obtain a precursor mixture.
[0017] Preferably, in step S103, the pH of the starch fiber solution is 2; and the pH of the MXene suspension solution is 7.
[0018] Preferably, the directional freeze casting in step S104 is obtained by performing directional freezing in a liquid nitrogen environment at -196°C for 30-60 minutes and then placing in a freeze dryer for 2-3 days.
[0019] Preferably, the gas phase crosslinking in step S104 is obtained by crosslinking in an oven at 40° C. using 25% glutaraldehyde vapor for 4 hours.
[0020] On the other hand, the present invention also provides an aerogel material based on protein fiber composite oligolayer MXene and its application in efficient photothermal evaporation synergistic marine uranium extraction.
[0021] The preparation method of the protein fiber composite oligolayer MXene aerogel provided by the present invention, on the one hand, utilizes electrostatic adsorption deposition to make the pea protein fiber composite oligolayer MXene, thereby improving the stability of the photothermal layer MXene; on the other hand, the porous aerogel through directional freeze casting has a directional vertical through-hole structure, which is not only conducive to the directional migration and discharge of salt, but also improves its salt resistance, and can also improve its photothermal conversion efficiency (85.9%) and solar evaporation rate (2.69kg m - 2 h -1 ), reducing operating and maintenance costs.
[0022] Furthermore, the porous aerogel honeycomb pore structure of the present invention has a uniform pore size distribution (80μm-1mm) and has excellent uranium ion adsorption. The composite material of the present invention can be used in the fields of efficient and stable solar thermal conversion, clean water production and uranium extraction, especially in the field of efficient photothermal evaporation and uranium ore resource extraction. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the preparation process of a protein fiber composite oligolayer MXene aerogel according to the present invention.
[0024] Figure 2 Photos of MXene suspensions with different mass concentrations.
[0025] Figure 3 XRD patterns of MXene, PPI-AF and PPI-AF@MXene.
[0026] Figure 4 a is the TEM image of PPI fiber morphology; 4b is the TEM image of MXene; 4c is the TEM image of PPI-AF@MXene.
[0027] Figure 5 a is the SEM top view of PPI-AF@MXene-Gel; 5b is the SEM side view of PPI-AF@MXene-Gel.
[0028] Figure 6 The mechanical properties test results of PPI-AF@MXene-Gel.
[0029] Figure 7 a is the UV-Vis-NIR absorption spectra of PPI-AF-Gel, PPI-AF-Gel@MXene and PPI-AF@MXene-Gel aerogels; 7b is the surface temperature distribution of PPI-AF-Gel, PPI-AF-Gel@MXene and PPI-AF@MXene-Gel aerogels (dry state) under single-sun irradiation; 7c is the surface temperature distribution of PPI-AF-Gel, PPI-AF-Gel@MXene and PPI-AF@MXene-Gel aerogels (wet state) under single-sun irradiation; 7d is the infrared thermal image of PPI-AF@MXene-Gel (dry state) under single-sun irradiation; 7e is the water evaporation performance of different aerogel samples under 1 sun intensity with pure water as a blank control experiment; 7f is the water evaporation performance of PPI-AF@MXene-Gel at different salt concentrations; 7g is a comparison of evaporation rate and energy conversion efficiency of different aerogel generators.
[0030] Figure 8 a is the ion concentration of PPI-AF@MXene-Gel aerogel before and after photothermal desalination of real seawater; 8b is the salt degradation experiment of PPI-AF@MXene-Gel aerogel; 8c is the cyclic (8h each time) evaporation performance of PPI-AF@MXene-Gel aerogel in 3.5wt% brine under one solar irradiation; 8d is the cyclic (8h each time) evaporation performance of PPI-AF-Gel@MXene aerogel in 3.5wt% brine under one solar irradiation; 8e is the performance comparison of different aerogel evaporators; 8f is the stability comparison diagram of PPI-AF@MXene-Gel and PPI-AF-Gel@MXene aerogel.
[0031] Fig. 9 a is the adsorption kinetics and fitting results of uranium by PPI-AF-Gel; Fig. 9 b shows the adsorption kinetics and fitting results of uranium on PPI-AF@MXene-Gel. DETAILED DESCRIPTION
[0032] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0033] Embodiment 1: Figure 1 , a method for preparing a protein fiber composite oligolayer MXene aerogel, comprising the following steps:
[0034] S101 extracts pea protein isolate by alkali dissolution and acid precipitation, and then uses simple heat treatment + ice bath cooling and room temperature incubation to prepare starch protein fiber (PPI-AF) solution: Pea protein isolate is dissolved in ultrapure water containing 150mM NaCl, and then the solution is adjusted to pH 2.0 with 6M hydrochloric acid and hydrated at 4°C for 16h. Then, the protein solution is centrifuged at 10000rpm for 20min, and the insoluble matter is filtered out with a 0.45μm filter to obtain a pea protein isolate solution with a mass concentration of 2wt%. The pea protein isolate solution is stirred at 250rpm in an oil bath at 85°C for 16h, and after heat treatment, it is immediately cooled in an ice bath and incubated at room temperature for 1 day to obtain a starch protein fiber (PPI-AF) solution.
[0035] S102 prepares MXene suspension by wet etching: First, 1.6g LiF (61.5mmoL) is completely dissolved in 20mL of 9M HCl aqueous solution to prepare an etching solution, and then 1g Ti3AlC2 is slowly added to the etching solution. After continuous stirring at 28°C for 24h, it is washed with ultrapure water several times until the pH of the mixture becomes 7. After the etching reaction is completed, the reaction product is washed with ultrapure water several times to remove the residual etching solution and by-products. In this process, continuous stirring and centrifugation are required to accelerate the washing effect. The pH value of the reaction product becomes neutral through washing and centrifugation. Then the neutral mixture is transferred to a clean and dry flask, filled with argon three times, ultrasonicated in an ice water bath for 2h, and then centrifuged at 3200 rpm for 1h, and the upper suspension is collected to obtain an 8mg / mL MXene suspension solution.
[0036] S103 uses electrostatic in-situ adsorption strategy to prepare aerogel precursor solution: 8 mL of starch protein fiber suspension (PPI-AF, pH 2) prepared by step S103 and 1 mL of MXene suspension solution (concentration 8 mg / mL, pH 7) are weighed and mixed evenly by magnetic stirring for 5 minutes to obtain PPI-AF@MXene precursor solution. The pH of PPI-AF@MXene precursor solution is tested to be 1-3.
[0037] S104 Preparation of PPI-AF@MXene-Gel aerogel by ice template freeze-drying: The PPI-AF@MXene solution was poured into a customized copper ice template mold with a diameter of 3.5 cm, and directionally frozen in a liquid nitrogen environment of -196°C for 30 minutes, and then placed in a freeze dryer for 2 days to obtain PPI-AF@MXene aerogel, which was cross-linked in an oven at 40°C using glutaraldehyde vapor with a mass concentration of 25% for 4 hours to obtain pea protein isolate starch fiber-based PPI-AF@MXene-Gel aerogel.
[0038] Example 2: The difference between Example 2 and Example 1 is the effect of the concentration of the MXene suspension solution added in step (3) on the material properties. The concentrations of the MXene suspension solutions are 1 mg / mL, 3 mg / mL, 5 mg / mL, 10 mg / mL, and 15 mg / mL, respectively.
[0039] Depend on Figure 2The results show that in the case of low deposition amount (ie, MXene concentration is less than 5 mg / mL), the content of photothermal material is relatively low, which directly leads to the lighter color of the material surface. The lack of its content will significantly affect the light absorption efficiency of the material. In the case of moderate deposition amount (ie, MXene concentration is in the range of 5-10 mg / mL), MXene can form a relatively uniform and stable deposition layer in the material. In the case of high deposition amount (ie, MXene concentration is higher than 10 mg / mL), MXene is prone to agglomeration during the deposition process. This is because as the MXene concentration increases, the interaction force between the nanosheets increases, making them more likely to attract each other and gather together. This agglomeration phenomenon causes the accumulated MXene sheets to form a thick layered structure, resulting in uneven distribution inside the material, resulting in poor stability. Therefore, the concentration of the MXene suspension solution is preferably 5-10 mg / mL.
[0040] Example 3: The difference between Example 3 and Example 1 is that the pH of the mixed solution of the starch protein fiber solution and the MXene suspension solution added in step (3) affects the material properties. Example 1 uses a protein fiber solution with a pH of 2 and a MXene suspension with a pH of 7 to obtain an acidic mixed solution (pH 1-3); Example 3 mixes a protein fiber solution with a pH of 2 and a MXene suspension with a pH of 7, and then adjusts the pH with 2M NaOH to obtain a neutral (pH 6-7) and alkaline (pH 9-10) mixed solution. From the results in Table 1, it can be seen that in a solution with a pH of 1-3, pea protein fiber will show good dispersibility, which is conducive to its deposition on the MXene surface. In a neutral or alkaline environment, MXene materials are easily corroded and decomposed by alkaline solutions, resulting in poor structural stability; at the same time, an alkaline environment may cause denaturation or precipitation of pea protein fibers, affecting the deposition effect.
[0041] Table 1 Effect of pH of MXene suspension solution on material properties
[0042]
[0043] In another embodiment, the starch protein fiber (PPI-AF) solution is obtained by fibrillating an 8 wt.% pea protein suspension solution (PPI).
[0044] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that in step S103, 8 mL of the fiber solution is freeze-dried using an ice template, and then cross-linked using 25% glutaraldehyde vapor in an oven at 40°C for 4 hours to obtain the PPI-AF-Gel aerogel, and then 1 mL of MXene solution is measured and spin-coated on the surface of the PPI-AF-Gel aerogel to obtain the PPI-AF-Gel@MXene aerogel.
[0045] Comparative Example 2: The difference between Comparative Example 1 and Example 1 is that steps S102 and S103 are omitted, and the starch protein fiber (PPI-AF) solution is directly freeze-dried and steam-crosslinked to obtain PPI-AF-Gel.
[0046] The performance of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 was characterized and tested, and the results are as follows:
[0047] (1) XRD tests were performed on PPI-AF, MXene and PPI-AF@MXene. Figure 3 The results showed that PPI-AF@MXene was successfully prepared.
[0048] (2) Scanning electron microscopy tests were performed on PPI-AF, MXene and PPI-AF@MXene. Figure 4 b The results can intuitively show that MXene is in a oligolayer form, and the starch protein fiber solution (PPI-AF) is in situ deposited on the surface of the oligolayer MXene (PPI-AF@MXene), which not only shows that PPI-AF is successfully composited on MXene, but also confirms the integrity of MXene, proving that the structure of MXene is not destroyed due to the composite PPI-AF.
[0049] (3) Scanning electron microscopy test of PPI-AF@MXene-Gel aerogel, Figure 5 It was found in a that the PPI-AF@MXene-Gel aerogel has a typical honeycomb pore structure with a uniform pore size distribution ranging from 80 μm to 1 mm. Figure 5 b Vertically aligned channels were found in PPI-AF@MXene-Gel aerogel, which is conducive to efficient photothermal evaporation and synergistic uranyl ion adsorption.
[0050] (4) The mechanical strength of PPI-AF@MXene-Gel was tested. Figure 6 In the experiment, PPI-AF@MXene-Gel showed excellent load-bearing capacity, which can withstand a weight of 1000g without any obvious damage, up to 5263 times its own weight. This is conducive to the stability of PPI-AF@MXene-Gel in long-term use.
[0051] (5) The photothermal evaporation performance of the PPI-AF-Gel of comparative example 2, the PPI-AF-Gel@MXene of comparative example 1 and the PPI-AF@MXene-Gel of example 1 were tested. The results are shown in Figure 7 , Figure 7a shows the UV-Vis-NIR absorption spectra of PPI-AF-Gel, PPI-AF-Gel@MXene and PPI-AF@MXene-Gel aerogels in the wavelength range of 300-2500nm. According to the evaluation results of the standard solar radiation spectrum (AM 1.5G), the light absorption rate of PPI-AF-Gel@MXene is only 88.6%, and the light absorption rate of PPI-AF-Gel without composite photothermal material is only 65.5%. The light absorption rate of PPI-AF@MXene-Gel is as high as 91.6%. Figure 7 As shown in b, after MXene compounding, the average stable temperature of the evaporator surface of PPI-AF-Gel@MXene and PPI-AF@MXene-Gel in the dry state was significantly increased from 43°C to 69°C and 72°C, respectively. Figure 7 As shown in Figure c, after MXene compounding, the average stable temperature of the evaporator surface of PPI-AF-Gel@MXene and PPI-AF@MXene-Gel in the wet state increased significantly from 33°C to 43°C and 45°C, respectively. Figure 7 As shown in Figure d, under simulated sunlight, the surface temperature of PPI-AF@MXene-Gel can quickly reach 45.3°C within 2 minutes at 1 sun intensity. Figure 7 The evaporation rate of PPI-AF@MXene-Gel shown in e is the highest, which is 2.69 kg m -2 h -1 The evaporation rate of PPI-AF-Gel@MXene is 2.05 kg m - 2 h -1 , the water evaporation rate of PPI-AF@MXene-Gel and PPI-AF-Gel@MXene evaporators in the dark is given by Figure 7 h calculated that under 1 sun irradiation, their solar energy conversion efficiencies were 85.9% and 84.9%, respectively, indicating that the PPI-AF@MXene-Gel sample has a significant advantage in photothermal conversion efficiency. Figure 7 f is the evaporation rate of the PPI-AF@MXene-Gel evaporator at different salt concentrations. The evaporation rate decreases with the increase of salt concentration. In 20 wt.% sodium chloride solution, the evaporation rate remains at 2.19 kg m -2 h -1 , indicating that the prepared material samples have excellent salt resistance.
[0052] (6) The actual seawater desalination capacity and salt resistance of PPI-AF@MXene-Gel aerogel were tested. The results are as follows Figure 8As shown in a, before and after the PPI-AF@MXene-Gel aerogel treated the real seawater samples from the South China Sea, the concentrations of the four main ions Ca2+, K+, Mg2+ and Na+ were significantly reduced by three to four orders of magnitude during the desalination process, making the water quality meet the drinking water standards set by the World Health Organization (WHO). Figure 8 The self-cleaning performance of PPI-AF@MXene-Gel aerogel can be observed in b, and 1g of salt is transferred back into the water within 1h. Figure 7 As shown in c, the evaporation rate of the PPI-AF@MXene-Gel evaporator is almost constant within 30 cycles (3.5 wt.% salinity, 8 h per cycle). -2 h -1 The above shows excellent durability. Figure 8 d shows that the evaporation rate of the PPI-AF-Gel@MXene evaporator showed a decreasing trend within 30 cycles (3.5 wt.% salinity, 8 h per cycle). Figure 8 f shows the color change of the two aerogel evaporators in 30 cycles. The color of the PPI-AF@MXene-Gel evaporator remains black after 30 cycles, while the color of the PPI-AF-Gel@MXene evaporator gradually becomes lighter after 30 cycles and finally returns to the color of the PPI-AF aerogel. This also proves that the stability of MXene is enhanced after covering it with starch fiber armor. Figure 8 e shows that compared with most aerogel evaporators, the PPI-AF@MXene-Gel evaporator has excellent evaporation rate and solar thermal conversion efficiency.
[0053] (7) The performance of PPI-AF@MXene-Gel aerogel in synergistic uranium extraction was evaluated by simulating seawater photothermal evaporation. Fig. 9 The results of a show that in 20 ppm uranium-added simulated seawater, the adsorption capacity of uranium in PPI-AF-Gel aerogel is 726.2 mg within 180 min of equilibrium time. - U / g, Fig. 9 b The results show that the adsorption capacity of uranium on PPI-AF@MXene-Gel aerogel is 833 mg within the equilibrium time of 180 min. - U / g. This indicates that the adsorption of uranium ions by PPI-AF@MXene-Gel aerogel is mainly physical adsorption, and the adsorption behavior fits well with the pseudo-first-order kinetic model, indicating that the PPI-AF@MXene-Gel aerogel prepared by this method has excellent uranium ion adsorption.
[0054] In summary, the preparation method of the protein fiber composite oligolayer MXene aerogel provided by the present invention improves the stability of the photothermal layer MXene by composite oligolayer MXene with pea protein fiber on the one hand; on the other hand, the porous aerogel with directional freeze casting has a directional vertical through-hole structure, which shows better performance than the disordered pore structure in terms of interface evaporation and salt resistance. It is not only conducive to the directional migration and discharge of salt, and improves salt resistance, but also improves its photothermal conversion efficiency and solar evaporation rate, and reduces operating costs and maintenance costs.
[0055] The composite material of the present invention can be used in the fields of efficient and stable solar thermal conversion, clean water production and uranium extraction, and has potential applications in the field of efficient photothermal evaporation and coordinated uranium ore resource extraction.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a protein fiber composite oligolayer MXene aerogel, characterized in that The following steps are involved: S101: taking 2-8 wt.% pea protein suspension solution and fibrillating it to obtain starch protein fiber suspension; S102 prepares 5 mg / mL-10 mg / mL MXene suspension; S103 uses an electrostatic adsorption strategy to in-situ deposit starch protein fibers on the surface of MXene to obtain a precursor mixture, wherein the pH of the precursor mixture is 1-3; S104 performs directional freeze casting and gas phase crosslinking on the precursor mixture to obtain an aerogel material.
2. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 1, characterized in that: In the step S101, the pea protein isolate is dissolved in ultrapure water containing NaCl, and then the pH of the solution is adjusted to 1-3 with hydrochloric acid, and then hydrated at 4° C. for 16 hours, centrifuged at a speed of 10,000 rpm for 20 minutes, and filtered to remove insoluble matter to obtain a pea protein isolate solution with a mass concentration of 2 wt.%, and then stirred at 250 rpm in an oil bath at 85° C. for 16 hours, cooled in an ice bath, and incubated at room temperature for 1 day to obtain a starch protein fiber solution.
3. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 1, characterized in that: In the step S102, LiF is weighed and completely dissolved in a hydrochloric acid solution to prepare an etching solution, and then Ti3AlC2 is slowly added to the etching solution, and the mixture is continuously stirred at 28°C for 24 hours and then washed until the pH value of the mixture becomes 7. After the reaction is completed, the reaction product is washed several times to make the pH value of the reaction product neutral, and then transferred to a clean and dry flask, filled with argon, and ultrasonicated in an ice bath for 2 hours and then centrifuged for 1 hour, and the upper suspension is collected to obtain a MXene suspension solution with a concentration of 8 mg / mL.
4. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 1, characterized in that: In the step S103, 8 mL of starch fiber solution and 1 mL of MXene suspension solution are weighed and stirred to mix evenly to obtain a precursor mixture.
5. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 4, characterized in that: In the step S103, the pH of the starch fiber solution is 2; and the pH of the MXene suspension solution is 7.
6. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 1, characterized in that: The directional freeze casting in step S104 is obtained by directional freezing in a liquid nitrogen environment at -196°C for 30-60 minutes and then placing in a freeze dryer for 2-3 days.
7. The method for preparing a protein fiber composite oligolayer MXene aerogel according to claim 1, characterized in that: The gas phase crosslinking in step S104 is specifically obtained by crosslinking with 25% glutaraldehyde vapor in an oven at 40° C. for 4 hours.
8. An aerogel material based on protein fiber composite oligolayer MXene, characterized in that: Prepared according to any one of claims 1 to 7.
9. Application of the aerogel material based on protein fiber composite oligolayer MXene as described in claim 8 in efficient photothermal evaporation synergistic marine uranium extraction.
Citation Information
Patent Citations
A solar interface evaporator based on starch-like plant protein fiber aerogel and its preparation method and application
CN117599435B
Preparation method of MXene-based composite aerogel
CN113101877A
Flexible MXene protein composite membrane with electromagnetic shielding and pressure-sensitive characteristics as well as preparation method and application of flexible MXene protein composite membrane
CN114702709A
Solar interface evaporator based on amyloid vegetable protein fiber aerogel as well as preparation method and application of solar interface evaporator
CN117599435A
High-temperature-resistant heat-insulating biomass aerogel and preparation method thereof
CN118165372A